2007
DOI: 10.1128/aem.01197-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analyses of Putative Sesquiterpene Synthase Genes in Phormidium sp. and Prevalence of geoA -Like Genes in a Drinking Water Reservoir

Abstract: The occurrence of taste and odor problems in drinking water supplies is a widespread phenomenon. From a Saxonian water reservoir we isolated a cyanobacterial species which was classified as Phormidium sp. Under laboratory conditions it produced an earthy-musty smell due to the synthesis of geosmin. The only genes shown to be involved in geosmin biosynthesis are cyc2 and geoA of Streptomyces. Based on the alignment of Cyc2 with a putative sesquiterpene synthase of Nostoc punctiforme, a degenerate primer pair wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Sequences from various cyanobacterial taxa are necessary to ascertain the occurrence of HGT in geosmin evolution and the role of HGT in the distribution of the geosmin synthase gene in cyanobacteria. However, geosmin-associated genes were only elucidated in a few strains, including N. punctiforme PCC 73102, Phormidium sp., and Lyngbya kuetzingii UTEX 1547 [11,13,29]. Figure S3), and could catalyze the FPP to sesquiterpenes, such as germacrene [12].…”
Section: Inconsistent Topologies Between Geosmin Gene and 16s Rdna Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences from various cyanobacterial taxa are necessary to ascertain the occurrence of HGT in geosmin evolution and the role of HGT in the distribution of the geosmin synthase gene in cyanobacteria. However, geosmin-associated genes were only elucidated in a few strains, including N. punctiforme PCC 73102, Phormidium sp., and Lyngbya kuetzingii UTEX 1547 [11,13,29]. Figure S3), and could catalyze the FPP to sesquiterpenes, such as germacrene [12].…”
Section: Inconsistent Topologies Between Geosmin Gene and 16s Rdna Phmentioning
confidence: 99%
“…According to Jiang et al [10], this type of cyclase is a bifunctional enzyme composed of two similar domains at the N-terminal and C-terminal positions, and FPP is converted to geosmin through the catalysis of these two domains. In cyanobacteria, two putative geosmin synthase genes (geoA1 and geoA2) homologous to sco6073 were identified from the geosmin-producing cyanobacterium, Phormidium sp., by using degenerating primers for PCR and reverse PCR [11]. Agger et al [12] and Giglio et al [13] cloned and successfully expressed the germacrene/germacradienol and geosmin synthase genes (npunmod) from the geosmin-producing cyanobacterium, Nostoc punctiforme PCC 73102, in Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…Since the same intermediates as in Streptomyces can be found in Calothrix as major components, the function of such an enzyme is also most likely for cyanobacteria. Experiments with a geosmin-forming Phormidium have shown that sesquiterpene synthase genes homologous to that of streptomycetes can be found in cyanobacteria (Ludwig et al, 2007). It is still an open question how a shift of the intracellular pattern of sesquiterpenes as observed for cultures of different age can be explained.…”
Section: Discussionmentioning
confidence: 99%
“…These primer sets are designed based on the reported cyanobacterial geosmin/MIB genes in geosmin-producing Phormidium sp. (Ludwig et al 2007), N. punctiforme PCC 73102 (Agger et al 2008;Giglio et al 2008), Lyngbya kuetzingii UTEX 1547 (Zhang et al 2014), Anabaena ucrainica (Wang et al 2015), and MIB-producing P s e u d a n a ba e n a s p . d q h 1 5 ( Wa n g e t a l .…”
Section: Cloning and Sequencing The Geosmin And Mib Synthesis Genesmentioning
confidence: 99%
“…Along with the development of modern biological technologies, the geosmin/MIB synthesis genes and the biochemical mechanisms in cyanobacteria have been found in a few filamentous species, i.e., geosmin-producing Phormidium sp. (Ludwig et al 2007), Nostoc punctiforme PCC 73102 (Agger et al 2 0 0 8 ; G i g l i o e t a l . 2 0 0 8 ) , a n d M I B -p r o d u c i n g Pseudanabaena sp.…”
Section: Introductionmentioning
confidence: 99%